Cross-curricular skills in the era of Sustainable Development Goals: Perception and Learning Outcomes among Students of the Faculty of Social Sciences and Communication (UPV/EHU) - Urbano Ortega, Isabel; Iturbe Tolosa, Andoni; del Castillo Aira, Itxaso (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The research analyzes the cross-cutting competencies developed in relation to employability and the SDGs during the training of the students of the Faculty of Social Sciences and Communication (UPV/EHU). The methodology, based on surveys, has measured through learning outcomes the relationship of critical thinking skills and social commitment with the SDGs. The results show that the learning outcomes of SDGs are at a very early stage, reduced to debate and reflection, far from initiatives with effective capacity for social transformation.